Facial emotion recognition among typically developing young children: A psychometric validation of a subset of NimStim stimuli. (March 2017) - Barnard-Brak, Lucy; Abby, Layla; Richman, David M.; Chesnut, Steven
Abstract: We evaluated the psychometric properties of NimStim taking into account the effects of chronological age on the ability of typically developing young children (aged 2–6 years old) to recognize basic facial expressions (i.e., happy, sad, angry, and fearful). We also examined the psychometric sufficiency of NimStim under race-matched and -mismatched facial emotion stimuli. In the current study, race-matched stimuli referred to when children with African American backgrounds received African American faces to rate their emotions and vice versa for race-mismatched stimuli. Results of the current study represent the first psychometric analysis of reliability and validity for using NimStim pictures depicting happy, sad, angry, and fearful with typically developing children aged 2–6 years old as well as examining race-matched versus -mismatched stimuli. Analyses revealed the psychometric sufficiency of a subset of pictures depicting happy, sad, angry, and fearful from NimStim among young children across race matched and mismatched stimuli. Highlights: Evaluated the psychometric properties of NimStim among typically developing young children. Evaluated ability to recognize basic facial expressions (i.e., happy, sad, angry, and fearful). Examined the psychometric sufficiency under race-matched and -mismatched facial emotion stimuli. First psychometric analysis of NimStim pictures for typically developing children with race-matched versus -mismatched stimuli.